2022
DOI: 10.1186/s12871-021-01556-7
|View full text |Cite
|
Sign up to set email alerts
|

Admission pattern, treatment outcomes, and associated factors for children admitted to pediatric intensive care unit of Tikur Anbessa specialized hospital, 2021: a retrospective cross-sectional study

Abstract: Background Assessement of the pattern of admission and treatment outcomes of critically ill pediatrics admitted to pediatric intensive care units (PICU) in developing countries is crucial. In these countries with resource limitations, it may help to identify priorities for resource mobilization that may improve patient service quality. The PICU mortality rate varies globally, depending on the facilities of the intensive care unit, availability of experties, and admission patterns. This study as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…The majority of the children admitted to this study (86.1%) were over the age of two. This finding is consistent with previous research in Ethiopia 25 , 26 and Mozambique. 16 A similar study in India found a different result than ours, in which more than 50.7% of the participants were infants.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The majority of the children admitted to this study (86.1%) were over the age of two. This finding is consistent with previous research in Ethiopia 25 , 26 and Mozambique. 16 A similar study in India found a different result than ours, in which more than 50.7% of the participants were infants.…”
Section: Discussionsupporting
confidence: 94%
“…This result is in line with other PICU studies that have been conducted in Ethiopia and have found mortality rates between 40% and 44%. 13,26 The death rate was 2%, 2.1%, and 4.5%, respectively, in similar studies conducted in India, Singapore, and Switzerland, but the findings were different. 27,28,30 Given that most families live in rural areas of the country with inadequate infrastructure and that most arrive at hospitals with advanced stages of illness after consulting traditional healers before going there, the disparity in mortality rates may be the result of a delay in seeking medical attention by the families of the children.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…An Egyptian study reported that the incidence of MODS in patients with severe sepsis and septic shock reached up to 68.9% [22] . The MODS was reported to be the most common cause of deaths in an Ethiopian PICU [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric intensive care services have been significantly increased in the poor countries since the start of the new century [2] . Nevertheless, many PICUs in the low-middle income countries (LMICs) lack organizational details [3] . Many units are still deficient in properly-trained medical staff, adequate nurse-topatients ratios, proper tools, monitoring capacity or ancillary assistance [4] .…”
Section: Introductionmentioning
confidence: 99%